Analisis Kualitas Air untuk Pengelolaan Sumber Daya Air Berkelanjutan dengan Pengujian Air Klorin - Susanto, Sony; Sigit Winarto; Zendy Bima Mahardana (Jurnal Pengabdian Masyarakat Waradin, 2025)
Sustainable water resource management in Indonesian villages is essential to address poor water quality and low public awareness. This program aims to enhance the knowledge and skills of the community regarding sustainable water resource management. The methods used include training and water quality testing across 14 parameters, such as lead, copper, iron, chromium, pH, and free chlorine, in accordance with the standards set by the Ministry of Health Regulation. Results showed a 40% increase in community understanding after training, with all tested water parameters found to be within safe limits. The program successfully engaged the community in water quality monitoring, raising awareness and encouraging participation in sustainable water resource management. Although some participants initially faced difficulties in using the testing tools, intensive guidance was provided to overcome these challenges. In conclusion, the program positively contributed to improving the community's knowledge, skills, and participation in maintaining better water quality in the village.